A Comparative Study On Clinical Profile Of Rsv And Non-Rsv Bronchiolitis Children Attending A Tertiary Care Centre (Journal of Pharmaceutical Negative Results, 2023)
Introduction: Acute bronchiolitis is a self-limiting lower airway disease affecting infants and children with Respiratory Syncytial Virus (RSV) being the most common causative organism accounting for 50%-80% of bronchiolitis cases. Other than RSV, viruses like parainfluenza, adenovirus, rhinovirus, human metapneumovirus can also cause bronchiolitis. Basic supportive treatment remains the cornerstone of management.Materials and Methods: This is a prospective study, conducted for a 6month period i.e from July 2021 to Dec 2021. The demographic characteristics and clinical features of children aged between 1 month to 3 years who fulfilled the inclusion criteria were noted in predesigned proforma. Nasopharyngeal swab was sent for viral analysis. Cases were then divided into RSV and non-RSV groups and clinical characteristics were compared.Results: Among 90 cases, RSV was positive in 50% cases. Fast breathing was significantly higher (57.5%) in non-RSV group. 68.8% of non-RSV cases had wheeze as compared to 31.3% of RSV cases that was statistically significant. No statistically significant difference was observed in other clinical parameters based on viral etiology. The duration of hospital stays and oxygen therapy was found to be higher in RSV positive cases.Conclusion: In children with bronchiolitis, clinical presentation and severity of disease didn’t differ between RSV and non-RSV infections. Virological testing may not have a role in clinical diagnosis or management except for isolation or minimizing the use of antibiotics.